2013
DOI: 10.1007/s11605-012-2121-1
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the Neutrophil–Lymphocyte Ratio (NLR) in Acute Pancreatitis: Identification of an Optimal NLR

Abstract: Elevation of the NLR during the first 48 h of admission is significantly associated with severe acute pancreatitis and is an independent negative prognostic indicator in AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
134
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 30 publications
7
134
0
6
Order By: Relevance
“…(21) The NLR, a new and inexpensive marker, provides a simple method to assess inflammatory status. High NLR values were found in cases of acute or chronic inflammation, such as acute pancreatitis, (22) chronic tonsillitis, (23) acute mesenteric ischaemia, (24) coronary artery disease, (9) heart failure, (10) diabetes mellitus (11) and other malignancies. (12,13) However, some limitations of our study should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…(21) The NLR, a new and inexpensive marker, provides a simple method to assess inflammatory status. High NLR values were found in cases of acute or chronic inflammation, such as acute pancreatitis, (22) chronic tonsillitis, (23) acute mesenteric ischaemia, (24) coronary artery disease, (9) heart failure, (10) diabetes mellitus (11) and other malignancies. (12,13) However, some limitations of our study should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [22] found that preoperative NLR was prognostic for gastric cancer patients. Suppiah et al [23] found that NLR elevation during the first 48 hours of admission was significantly associated with severe acute pancreatitis, and was an independent (negative) prognostic factor. Kahramanca et al [24] found preoperative NLR useful in the diagnosis of acute appendicitis, as well as in the differentiation of patients with simple and complicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…The principle behind NLR is that neutrophil levels rise as part of the inflammatory cascade, whereas lymphocytes are depleted during sepsis. Measuring the divergence between these 2 WBC components is believed to be more accurate at predicting poor clinical outcome than measuring each one individually [12] . A recent retrospective study by Hogan et al [13] assessed the role of NLR in the setting of acute diverticulitis.…”
Section: Introductionmentioning
confidence: 99%